THE INFLUENCE OF TAX LITERACY AND TAXPAYER AWARENESS ON COMMUNITY PARTICIPATION IN PAYING LAND AND BUILDING TAXES - M. Tio Riyando; Ratih Kusumatuti; Derist Touriano (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The objective of this research is to examine the impact of tax literacy and taxpayer awareness on compliance in the payment of land and building taxes. Primary data, gathered through questionnaires, was collected in the Danau Teluk Jambi City district. The statistical method employed for analysis was multiple regression. The findings reveal that the individual attitude of the taxpayer has no significant influence on taxpayer compliance. However, taxpayer awareness and taxation knowledge both have significant effects on taxpayer compliance. Additionally, when considering taxpayer attitudes, awareness, and taxation knowledge together, they collectively exhibit a significant impact on taxpayer compliance. The results of the study reveal that in Danau Teluk District, there is a noteworthy correlation between taxpayers' compliance in settling land and building taxes and their level of awareness. Specifically, taxpayers who demonstrate a higher awareness level are more likely to exhibit greater compliance in meeting their tax obligations. Additionally, the study underscores that tax literacy plays a substantial role in influencing taxpayers' responsibility in fulfilling their land and building tax liabilities within the same district. In essence, individuals with a more comprehensive understanding of tax-related matters are inclined to display a heightened sense of obligation when it comes to fulfilling their tax responsibilities for land and building properties.